2006
DOI: 10.1177/0148607106030003231
|View full text |Cite
|
Sign up to set email alerts
|

Application Criteria of Enteral Nutrition in Patients With Anorexia Nervosa: Correlation Between Clinical and Psychological Data in a“ Lifesaving” Treatment

Abstract: Besides defining minimal criteria for a "lifesaving" cure and proposing 2 ad hoc scales for the assessment of patients' subjective willingness toward feeding and for the objective measurement of feeding itself, clinical data and correlations with psychological data evidenced the importance of artificial nutrition and specifically of enteral nutrition as a therapeutic tool, allowing us to define the modalities of implementation of enteral nutrition. Results show that, because enteral nutrition did not deteriora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 33 publications
0
33
1
8
Order By: Relevance
“…EN showed beneficial effects in improving nutritional status of AN patients [6 -8]. However EN could cause feeling of fullness and other dyspeptic symptoms, exacerbated by the delayed gastric emptying complained of by many AN patients [8]. Because of dyspeptic symptoms, nasogastric feeding can interfere with the normal oral consumption of calories and discourage normal eating patterns [9 -11].…”
mentioning
confidence: 99%
“…EN showed beneficial effects in improving nutritional status of AN patients [6 -8]. However EN could cause feeling of fullness and other dyspeptic symptoms, exacerbated by the delayed gastric emptying complained of by many AN patients [8]. Because of dyspeptic symptoms, nasogastric feeding can interfere with the normal oral consumption of calories and discourage normal eating patterns [9 -11].…”
mentioning
confidence: 99%
“…The first line is generally to initiate refeeding patients with food, progressing to oral intake of high calorie liquid supplements, followed by NG tube feeds. Studies have shown minimal psychiatric distress and rapid, significant weight gain when using NG tube to feed patients with eating disorders [7,8,[15][16][17][18][19]. Surgical placement of a gastrostomy tube is an option at the invasive end of the spectrum; however, in the five cases described, it appears to have been an effective intervention.…”
Section: Discussionmentioning
confidence: 96%
“…Los estudios realizados difieren en cuanto al hincapié que hacen en aspectos psicológicos y nutricionales del tratamiento, siendo necesario que las indicaciones de nutrición artificial los contemplen, incluyendo la definición de riesgo vital a la hora de aplicar esta modalidad de tratamiento, grado de aceptación del tratamiento, tipo de tratamiento (enteral o parenteral), indicadores de eficacia o resultados esperados durante el seguimiento y efectos (psicológicos, en función de la edad, etc.) 71 .…”
Section: Nutrición Artificialunclassified